EFFECT OF CATFISH (Clarias sp.) PROTEIN CONCENTRATE ON THE ORGANOLAPTIC QUALITY OF DRIED CAKE - M ikhsan satriadi; Syahrul Syahrul; Dian iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT            The aim of this study was to determine the effect of catfish with diferent concentrations, on the organolaptic quality of consumer acceptance towards dried cake (bangkit cake). The method in this research is an experiment with a non-factorial Completely Randomized Design (CRD) with 4 treatment levels, namely 0% (F0), 5% (F1), 10% (F2), and 15% (F3). The parameter was measurd for organolaptic test (appearance, texture, taste and aroma), based on the result F2 treatment was the best teratment, most favorable by consumer acceptence, wherein appearance 3,78; textured 4.34; taste 3,34; aroma 3,54.Keywords:fortification, catfish  (Clarias sp.), dried cake